Effect of Moringa Leaf Extract in Inhibiting Lung Fibrosis in Wistar Rats with Diabetic Model - Zaenab, Zahrina Isnandia; Suryono, Suryono; Aziz, Ayu Munawaroh (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Uncontrolled diabetes can lead to macrovascular and microvascular complications in various organs. Organ fibrosis is one of the microvascular complications due to diabetes. Hyperglycemia triggers ROS formation thereby causing oxidative stress. Oxidative stress enhances pro-inflammatory and pro-fibrotic activities. The lungs have a lot of vascularization and connective tissue, making them susceptible to diabetes complications. Moringa is called 'The Miracle Tree' because it has many properties. Moringa leaves are the most studied part, for their efficacy as antioxidants. This study examines the effect of moringa leaf extract (MLE) in inhibiting lung fibrosis in diabetic Wistar rats.Methods: A total of 27 male Wistar rats were randomized into three groups, K0, K1 and P. Group K0 was given saline (ip) and saline (orally); K1 was given Streptozotocin (STZ) (ip) and saline (orally); P was given STZ (ip) and MLE (orally). MLE was administered daily at 1000 mg/Kg BW dose for four weeks. Lung fibrosis assessment was carried out using a modified Ashcroft scale.Results: Lung fibrosis assessment showed that the K1 group had the highest mean of lung fibrosis and K0 had the lowest mean of lung fibrosis. Kruskal-Wallis test showed that there was a significant difference in the data comparison between the three groups. The post-hoc test showed that there was a significant difference in the data comparison between groups. Comparison of the K0-K1 group data showed the smallest significance value and comparison of the K0-P group data showed the highest significance value. Conclusion: MLE can inhibit lung fibrosis in diabetic Wistar rats.